The Role of Emotional Quotient in Enhancing Employee Performance and Organizational Success in the Service Industry - Abbas, Bakhtiar; Bagea, Arfin; Budhihard, Andi M.; Nur, Muh.; Sutrino, Anas (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The service industry heavily relies on the quality of service provided by employees, with Emotional Quotient (EQ) playing a crucial role in enhancing individual performance and organizational effectiveness. While EI is widely recognized as a key factor in improving workplace interactions and customer satisfaction, many organizations still prioritize technical skills over emotional and interpersonal development. This study examines the role of EQ in the service industry, focusing on its impact on both individual and organizational performance. It explores EQ dimensions, challenges in its development, and strategies for enhancing human resource quality to foster a harmonious and productive work environment. A qualitative descriptive approach is employed, utilizing in-depth interviews with human resource managers, supervisors, customer service employees, academics, and industrial psychologists to analyze the relationship between EQ and employee performance. The findings reveal that EQ not only enhances employees' ability to manage stress and build interpersonal relationships but also plays a strategic role in improving leadership effectiveness and customer service quality. This study underscores the importance of integrating EQ into human resource management policies to cultivate a more adaptive, productive, and sustainable work environment in the service industry.